NPAS2 Compensates for Loss of CLOCK in Peripheral Circadian Oscillators. - Dominic Landgraf; Lexie L Wang; Tanja Diemer; David K Welsh (PLoS Genetics, 2016)
Heterodimers of CLOCK and BMAL1 are the major transcriptional activators of the mammalian circadian clock. Because the paralog NPAS2 can substitute for CLOCK in the suprachiasmatic nucleus (SCN), the master circadian pacemaker, CLOCK-deficient mice maintain circadian rhythms in behavior and in tissues in vivo. However, when isolated from the SCN, CLOCK-deficient peripheral tissues are reportedly arrhythmic, suggesting a fundamental difference in circadian clock function between SCN and peripheral tissues. Surprisingly, however, using luminometry and single-cell bioluminescence imaging of PER2 expression, we now find that CLOCK-deficient dispersed SCN neurons and peripheral cells exhibit similarly stable, autonomous circadian rhythms in vitro. In CLOCK-deficient fibroblasts, knockdown of Npas2 leads to arrhythmicity, suggesting that NPAS2 can compensate for loss of CLOCK in peripheral cells as well as in SCN. Our data overturn the notion of an SCN-specific role for NPAS2 in the molecular circadian clock, and instead indicate that, at the cellular level, the core loops of SCN neuron and peripheral cell circadian clocks are fundamentally similar.